High-frequency surface currents induced on a perfectly conducting cylindrical reflector - Idemen, M.; Buyukaksoy, A. (Institute of Electrical and Electronics Engineers (IEEE), 1984)
An explicit expression for the surface current induced by sources on a perfectly conducting cylindrical reflector is obtained by taking into account the locality of the high-frequency diffraction phenomenon. The results show that the component previously conjectured by Ufimtsev involves several components having different propagation behaviors that can be separated into three main groups. When the reflector becomes infinitely large, the currents excited by edge diffraction are shown to reduce to those for the classical half-plane problem. The results are independent of the actual source configuration and may thus be useful in more complicated situations.